Regulation of Reactive Oxygen Species by Sodium Selenite in AndroMed® Extender Enhances Post-Thaw Saanen Buck Semen Quality - Caterina Palma Erlindra; Dio Fico Felsidan Diatmono; Fransisca Gani Padmawati; Arina Dinar Nurfadilla Sastranegara; Pradita Iustitia Sitaresmi; Sigit Bintara; Diah Tri Widayati (Universitas Sebelas Maret, 2026)
Semen cryopreservation is known to cause considerable damage to spermatozoa through the generation of free radicals. This damage can potentially be mitigated by the use of potent antioxidants, such as sodium selenite, which does not impair semen quality when administered in small doses. This study aimed to assess the impact of low-dose sodium selenite supplementation on post-thaw semen quality in Saanen bucks. Semen was collected from 2 superior Saanen bucks and evaluated according to standard criteria before dilution and freezing. Cryopreserved semen was stored in liquid nitrogen (LN2) at a temperature of -196 °C for 90 days. The experimental treatments involved the addition of sodium selenite to the AndroMed® diluent medium at 3 different concentrations: without supplementation/control (C), 5 ppm (T1), and 10 ppm (T2). Frozen semen was thawed at 37 °C in a water bath for 30 seconds before post-thaw quality assessment. The parameters assessed included motility, viability, abnormalities, plasma membrane integrity (PMI), acrosome membrane integrity (AMI), and reactive oxygen species (ROS). The data were statistically analyzed using One-Way analysis of variance (ANOVA). The results showed that the addition of sodium selenite had a significant effect (p < 0.05) on motility, viability, PMI, AMI, and ROS production, but did not affect the abnormality (p > 0.05). Interestingly, T1 resulted in the most substantial improvements, yielding the highest percentages of post-thaw motility (71.81±1.05%), viability (73.36±1.08%), PMI (77.49±1.68%), and AMI (79.29±0.63%), as well as the lowest ROS production (13.67±0.50%). In conclusion, the addition of 5 ppm sodium selenite enhances post-thaw semen quality in Saanen bucks.